Influence of backbone curvature on the organic electrochemical transistor performance of glycolated donor-acceptor conjugated polymers - Ding,B; Kim,G; Kim,Y; Eisner,FD; Gutierrez-Fernandez,E; Martin,J; Yoon,M-H; Heeney,M (Angewandte Chemie International Edition, 2021)
Two new glycolated semiconducting polymers PgBT(F)2gT and PgBT(F)2gTT of differing backbone curvatures were designed and synthesised for application as p-type accumulation mode organic electrochemical transistor (OECT) materials. Both polymers demonstrated stable and reversible oxidation, accessible within the aqueous electrochemical window, to generate polaronic charge carriers. OECTs fabricated from PgBT(F)2gT featuring a curved backbone geometry attained a higher volumetric capacitance of 170F cm−3. However, PgBT(F)2gTT with a linear backbone displayed overall superior OECT performance with a normalised peak transconductance of 3.00×104mS cm−1, owing to its enhanced order, expediting the charge mobility to 0.931cm2 V−1 s−1.